2018
DOI: 10.1159/000489966
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pattern Recognition Receptor Expression and Functionality in Liver Primary Cells and Derived Cell Lines

Abstract: Different liver cell types are endowed with immunological properties, including cell-intrinsic innate immune functions that are important to initially control pathogen infections. However, a full landscape of expression and functionality of the innate immune signaling pathways in the major human liver cells is still missing. In order to comparatively characterize these pathways, we purified primary human hepatocytes, hepatic stellate cells, liver sinusoidal endothelial cells (LSEC), and Kupffer cells (KC) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 48 publications
(59 reference statements)
0
43
0
Order By: Relevance
“…As previously described, even in this tolerant environment, liver MΦ are able to respond to the detection of specific pathogens . Liver MΦ express a large spectrum of PRR, among which, TLR1/2, TLR2/6, TLR3, TLR4, TLR8 and RIGI/MDA5, leading, after stimulation, to the secretion of a large spectrum of immune factors such as ROS, cytokines (IL‐6, IL‐10, IL‐12, TNFα…) and chemokines (CCL3, CCL5…) among others . Liver MΦ have also been described to be functional for several inflammasomes (AIM2, NLRP3), which, upon stimulation, induce the production, maturation and secretion of IL‐1β and IL‐18 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…As previously described, even in this tolerant environment, liver MΦ are able to respond to the detection of specific pathogens . Liver MΦ express a large spectrum of PRR, among which, TLR1/2, TLR2/6, TLR3, TLR4, TLR8 and RIGI/MDA5, leading, after stimulation, to the secretion of a large spectrum of immune factors such as ROS, cytokines (IL‐6, IL‐10, IL‐12, TNFα…) and chemokines (CCL3, CCL5…) among others . Liver MΦ have also been described to be functional for several inflammasomes (AIM2, NLRP3), which, upon stimulation, induce the production, maturation and secretion of IL‐1β and IL‐18 .…”
Section: Introductionmentioning
confidence: 88%
“…A study in Pekin duck revealed that minutes after inoculation, HBV was taken up by liver MΦ, highlighting their interaction in vivo . As a DNA virus with RNA intermediates, HBV could theoretically be recognized by several PRR expressed by liver MΦ such as TLR3 or RIGI/MDA5 as well as some cytosolic DNA sensors . However, the recognition of HBV nucleic acids may be impaired by (i) the physical separation of encapsidated rcDNA (relaxed circular DNA, a partially double stranded DNA) from cytosolic DNA sensors, and (ii) the resemblance between HBV RNAs and host mRNAs as viral RNAs are transcribed by the host polymerase.…”
Section: Interaction Between Liver Mφ and Hbvmentioning
confidence: 99%
“…6,7 Several pathogen recognition receptors (PRRs) are strongly expressed by hepatocytes. 8 Upon encountering pathogen-associated molecular patterns (PAMPs), hepatocytes readily secrete inflammatory cytokines, which help control the spread and growth of pathogens. 9 Owing to their abundance in the liver and known immune functions, we aimed to investigate the direct/indirect antiviral mechanisms employed by hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, R-848 concentration was increased from 1 µg/ml in RAW 264.7 cells to 10 µg/ml in THP-1 to achieve at least some TNF production (about 100 pg/ml, not shown); CLO75 concentration was maintained at 10 µg/ml as in RAW cells since already high, after verifying that it induced some TNF production also in THP-1 cells (about 30 pg/ml, not shown). Low expression of TLR7 and TLR8 in THP-1 cells, and low sensitivity to stimulation with TLR7/8 agonists, have been previously reported [25,27].…”
Section: Differential Induction Of Prdx1 Txnrd1 and Hmox1 By Tlr Agomentioning
confidence: 65%